Answer:
g(3) = 13
Step-by-step explanation:
The function g(3) means you replace every x value in the g(x) equation with 3:
![g(x) = x^2 + 4\\g(3) = 3^2 + 4\\g(3) = 9 + 4\\g(3) = 13](https://tex.z-dn.net/?f=g%28x%29%20%3D%20x%5E2%20%2B%204%5C%5Cg%283%29%20%3D%203%5E2%20%2B%204%5C%5Cg%283%29%20%3D%209%20%2B%204%5C%5Cg%283%29%20%3D%2013)
Hope this helps!
Answer:
-2
Assumption:
Find the value of x such that
.
Step-by-step explanation:
![(f+g)(x)=0](https://tex.z-dn.net/?f=%28f%2Bg%29%28x%29%3D0)
![f(x)+g(x)=0](https://tex.z-dn.net/?f=f%28x%29%2Bg%28x%29%3D0)
![(x^2-2x)+(6x+4)=0](https://tex.z-dn.net/?f=%28x%5E2-2x%29%2B%286x%2B4%29%3D0)
Combine like terms:
![x^2+4x+4=0](https://tex.z-dn.net/?f=x%5E2%2B4x%2B4%3D0)
This is not too bad too factor on the left hand side since 2(2)=4 and 2+2=4.
![(x+2)(x+2)=0](https://tex.z-dn.net/?f=%28x%2B2%29%28x%2B2%29%3D0)
![(x+2)^2=0](https://tex.z-dn.net/?f=%28x%2B2%29%5E2%3D0)
So we need to solve:
![x+2=0](https://tex.z-dn.net/?f=x%2B2%3D0)
Subtract 2 on both sides:
![x=-2](https://tex.z-dn.net/?f=x%3D-2)
Let's check:
![(f+g)(-2)](https://tex.z-dn.net/?f=%28f%2Bg%29%28-2%29)
![f(-2)+g(-2)](https://tex.z-dn.net/?f=f%28-2%29%2Bg%28-2%29)
![((-2)^2-2(-2))+(6(-2)+4)](https://tex.z-dn.net/?f=%28%28-2%29%5E2-2%28-2%29%29%2B%286%28-2%29%2B4%29)
![(4+4)+(-12+4)](https://tex.z-dn.net/?f=%284%2B4%29%2B%28-12%2B4%29)
![(8)+(-8)](https://tex.z-dn.net/?f=%288%29%2B%28-8%29)
![0](https://tex.z-dn.net/?f=0)
0 was the desired output of
.
Answer:
D) 5/8
Step-by-step explanation:
Since Susie has 5 books and 8 hair pins, you get 5:8 which can be transferred into a fraction of 5/8.
Answer: 36 days
Step-by-step explanation:
that’s the lowest multiple of 9 that also is a multiple of 12. It’s the LCF aka Least Common Factor
The slope is the number before x, so -3